MathCityMap Application in Mathematics Learning in Primary School - Ema Astri Muliasari; Cicin Solihati Firizki; Rina Nur Rahayu; Karlimah Karlimah; Erwin Rahayu Saputra; Syarip Hidayat (Universitas Sebelas Maret, 2023)
The background of this research is that the use of digital technology in learning mathematics in schools has not been optimal. The purpose of this research is to improve mathematics learning outcomes by utilizing technology through the MathCityMap application in teaching geometry in elementary schools. Methods This research uses classroom action research which is carried out in two cycles The subject was a population of 68 grade five students in an elementary school in West Java, using descriptive statistics. Data collection techniques using questionnaires, observations, tests, and, documentation studies. The results of this study indicate an increase in mathematics learning outcomes. In pre-cycle 58.05, it increased in cycle 1 to 72.03 and increased again in cycle 2 to 89.60.The results of observations show that the use of digital technology has the potential to support teachers in facilitating the teaching and learning process of mathematics outdoors so that students gain direct mathematical experience and deal with the real world. Based on these results, MathCityMap is proven to be able to improve mathematics learning outcomes for elementary school students, especially in teaching geometry.